The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000490078
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from MiR-30d-5p-ADSCs Reverse Acute Ischemic Stroke-Induced, Autophagy-Mediated Brain Injury by Promoting M2 Microglial/Macrophage Polarization

Abstract: Background/Aims: Recent studies have indicated that exosomes secreted from adipose-derived stem cells (ADSCs) have important effects in the treatment of ischemic injury. However, the treatment mechanism is unclear. This study aimed to investigate whether ADSC-derived exosomes enriched with microRNA (miR)-30d-5p have a protective effect on acute ischemic stroke (AIS). Methods: In the current study, inflammatory factors and miR-30d-5p expression were assessed in 70 subjects with AIS and 35 healthy controls. Exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
208
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(210 citation statements)
references
References 44 publications
2
208
0
Order By: Relevance
“…Notable studies have reported that BM-MSC exosomes could repair spinal cord injury by suppressing the activation of A1 neurotoxic reactive astrocytes induced by activated microglia (86) or by inhibiting the complement system (105) and the NF-κB signaling pathway (46,57,105). Meanwhile, SC-EVs have been observed to polarize microglia from classic M1 to antiinflammatory M2 phenotypes (59,85,106,107), which might be attributed to the targeted suppression of the 3 ′ -UTR mRNA expression in Beclin-1 and Atg5 and inhibition of autophagymediated microglial polarization toward pro-inflammatory state by miR-30d-5p-expressing EVs (59) ( Table 1). Thus, SC-EVs create a microenvironment conducive to nerve cell repair by inducing expression of microglial immunotolerance phenotypes in NS diseases.…”
Section: Stem Cell-derived Extracellular Vesicle Regulatory Potentialmentioning
confidence: 99%
“…Notable studies have reported that BM-MSC exosomes could repair spinal cord injury by suppressing the activation of A1 neurotoxic reactive astrocytes induced by activated microglia (86) or by inhibiting the complement system (105) and the NF-κB signaling pathway (46,57,105). Meanwhile, SC-EVs have been observed to polarize microglia from classic M1 to antiinflammatory M2 phenotypes (59,85,106,107), which might be attributed to the targeted suppression of the 3 ′ -UTR mRNA expression in Beclin-1 and Atg5 and inhibition of autophagymediated microglial polarization toward pro-inflammatory state by miR-30d-5p-expressing EVs (59) ( Table 1). Thus, SC-EVs create a microenvironment conducive to nerve cell repair by inducing expression of microglial immunotolerance phenotypes in NS diseases.…”
Section: Stem Cell-derived Extracellular Vesicle Regulatory Potentialmentioning
confidence: 99%
“…miR-499 is also important in ischemic postconditioning following cardiac challenge by ischemia-reperfusion [42]. miR-30d-5p oxerexpression limits ischemic injury and has demonstrated experimental ischemic protection in other tissues [43]. miR-490-3p is anti-atherosclerotic in human coronary artery smooth muscle cells [44].…”
Section: Protective Mechanisms Relevant To Diving In Each Tissuementioning
confidence: 99%
“…Generally, EVs can promote myocardial regeneration and restore cardiac function by directly activating cardiac precursor cells and inducing their differentiation, through the promotion of cardiomyocytes survival and proliferation. EVs are also able to inhibit cardiomyocytes apoptosis, to stimulate angiogenesis, and finally to regulate the inflammatory response in the damaged area [166][167][168][169]. One of the possible mechanism is related to the increase in cardiomyocytes of Bcl-2 expression, responsible for reduction of cardiac cell apoptosis, promotion of proliferation and angiogenesis [170].…”
Section: Extracellular Vesicles-based Regenerative Medicinementioning
confidence: 99%
“…Other miRNAs involved in myocardium protection are miRNA-21a-5p, miRNA -21, miRNA-125-5p and miRNA93-5p [174][175][176][177]. Besides, overexpression of miRNA-30d inhibited autophagy and promoted polarization of macrophages into the anti-inflammatory M2 type [169]. The expression of inflammatory factors was also down-regulated by the miRNA-126 [178].…”
Section: Extracellular Vesicles-based Regenerative Medicinementioning
confidence: 99%